The Life and Work of Rosalba Carriera (1673-1757) : The Queen of Pastel - Oberer, Angela (Visual and material culture, 1300-1700., 2020)
The Life and Work of Rosalba Carriera (1673-1757). The Queen of Pastel is the first extensive biographical narrative in English of Rosalba Carriera. It is also the first scholarly investigation into the external and internal factors that helped to create this female painter's unique career in eighteenth-century Europe. It documents the difficulties, complications, and consequences that arose then-and can also arise today-when a woman decides to become an independent artist. This book contributes a new, in-depth analysis of the interplay among society's expectations, generally accepted codices for gendered behavior, and one single female painter's astute strategies for achieving success, as well as autonomy in her professional life as a famed artist. Some of the questions that the author raises are: How did Carriera manage to build up her career? How did she run her business and organize her own workshop? What kind of artist was Carriera? Finally, what do her self-portraits reveal in terms of self-enactment, possibly autobiographical turning points?